Penerapan Intervensi Psikososial dalam Pelayanan Terhadap Anak Korban Kekerasan Seksual di Lembaga Perlindungan Anak Deli Serdang - Muhammad Raghib; Husni Thamrin; Hairani Siregar (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Child sexual abuse is a severe problem that profoundly affects victims’ physical, psychological, and social well-being. The Deli Serdang Child Protection Institution (LPA) functions as a non-governmental organization providing recovery and rehabilitation services for victims of such abuse. This study aims to examine the implementation of psychosocial interventions for child sexual abuse victims at LPA Deli Serdang. Conducted in Deli Serdang Regency, the research involved several informants, including the Chairperson and Psychologist of LPA as key informants, two child victims identified by the initials Z and N as main informants, and four supporting informants consisting of the victims’ parents, the LPA Secretary, and Legal Staff. Data collection was carried out through literature review, observation, in-depth interviews, and documentation. The data were analyzed qualitatively to gain a comprehensive understanding of the psychosocial intervention process. The findings show that LPA Deli Serdang has fulfilled its role in accordance with Law No. 35 of 2014 on Child Protection, particularly in providing integrated services that address victims’ emotional and behavioral needs. Based on Nitimiharjo’s (2012) framework, psychosocial interventions implemented by LPA have contributed to positive improvements in the victims’ cognitive, emotional, behavioral, and environmental domains. Moreover, according to Caroline’s (2012) theory, individual and play therapy have been identified as the primary methods used to assist victims in the recovery process. Overall, these interventions have proven effective in supporting psychological healing and social reintegration for child sexual abuse victims under the institution’s care.